Validação de kit imunocromatográfico rápido para diagnóstico da Hepatite C - Lima, Jéssica Caldeira de (Universidade Federal de São Carlos, 2019)
Hepatitis C is an infectious disease caused by the Hepatitis C Virus (HCV) and usually asymptomatic in the acute phase. Globally, an estimated 71 million people are infected with HCV and approximately 400,000 deaths happen annually due to complications from the disease, such as cirrhosis and liver cancer. This study aimed to develop and validate a rapid immunochromatographic test for the detection of anti-HCV antibodies, the Imuno-Rápido HCV, by comparing the performance of this product with a second commercially available test (Commercial A) with the same methodology and ELISA methodology (Murex anti-HCV 4.0, DiaSorin) considered gold standard. Tests for validation include repeatability and reproducibility analysis, real-time and accelerated stability analysis, clinical sensitivity and specificity measurements, and positive and negative predictive values. In this study, 383 samples characterized by ELISA methodology were included and, by comparing the results, the clinical sensitivity and specificity parameters, positive and negative predictive values for the immunochromatographic tests Imuno-Rápido HCV and Commercial A were measured. For both immunochromatographic tests, a value of 100% were found for clinical sensitivity and negative predictive value. Clinical specificity values were 99.7% for Imuno-Rápido HCV and 100% for Commercial A test and positive predictive values for these kits were 98.6% and 100%, respectively. Repeatability and reproducibility analyzes showed concordant results in 100% of the tests, and real-time and accelerated stability assessments demonstrated the ability of the kit to maintain its proper functioning over time even under temperature stress, suggesting its ability to maintain stable for at least 18 months. These results corroborate the hypothesis that the Imuno-Rápido HCV has performance similar to commercially available kits that use the same methodology and is able to assist in the diagnosis of HCV infection safely and quickly, combined with easy execution and low cost.
Validation of rapid immunochromatographic assay for diagnosis of hepatitis C
Keywords: Hepatite C; Diagnóstico; Imunocromatografia; Point of care; Validação; Hepatitis C; Diagnosis; Immunochromatography; Validation; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::BIOQUIMICA; CIENCIAS BIOLOGICAS::IMUNOLOGIA